ANALYSIS OF BUSINESS DEVELOPMENT AND TURNOVER STRATEGIES RECEIVABLES TO INCREASE EFFICIENCY CAPITAL WORK - Tri Hardiyanti; Vidya Fathimah (Jurnal Ekonomi, 2023)
This study aims to determine the business development strategy and performance of accounts receivable turnover in increasing the efficiency of CV. Tempe Budi Berkah's working capital. Researchers use a type of qualitative research, and data obtained directly from the research object or primary. The sampling technique uses non-probability sampling with SWOT analysis as an analytical technique and the results of the analysis will be described. The results of the analysis that has been carried out by researchers are CV. Budi Berkah Tempe has done good business development by practicing SWOT analysis in its business and already has many customers and has good accounts receivable turnover, which is above 10 times a year, so as to increase working capital efficiency.